1106. A Retrospective Assessment of the Effects of Baricitinib and Tocilizumab on COVID-19 Patients requiring High Flow Oxygen. (15th December 2022) - Tin, Kathy; Fernandes, Annamarie; Njoroge, Alexander; Go, Roderick
Abstract: Background: SARS-CoV-2 has been a leading cause of mortality worldwide for over two years. It continues to be a group effort to discover treatment to prevent further deterioration during the disease course. Positive outcomes have been observed in select patients with immune modulator therapy. Although large randomized controlled trials have investigated the use of immunomodulators in COVID-19 therapy, few have compared the differences in safety profiles and clinical outcomes between the different drugs. We studied the differences in outcomes in hospitalized patients with COVID-19 pneumonia treated with baricitinib versus tocilizumab. Methods: Adult patients admitted to Stony Brook University Hospital between April 2020 and April 2021 with high flow oxygen requirements due to severe COVID-19 pneumonia were retrospectively analyzed. The primary endpoint was the time to reduction of highest oxygen requirement 14 days after immune modulator therapy was administered or hospital discharge, whichever came first. Secondary endpoints include length of hospital stay (LOS), 28-day mortality, and serious adverse events. Results: 132 patients with COVID-19 pneumonia were treated with immune modulators. One patient was excluded from primary and secondary analysis due to having received both tocilizumab and baricitinib. All patients received steroids and remdesivir. 73 received baricitinib and 58 received tocilizumab. Oxygen requirements at the initiation of either baricitnib or tocilizumab had a mean of 5.84±0.6 and 5.9±0.7, respectively using the WHO ordinal scale. The mean time to oxygen down titration in the baricitinib group was similar (5.7±2.6 and 6.07±2.7 days). In continuous variable analysis, patients who received baricitinib had a longer duration of fever (6.0 days vs 3.6 days, p=0.04) and lower serum ferritin (909.9 ng/ml vs. 1331.8 ng/ml, p=0.09). LOS was not similar between the groups (mean 24.4 vs. 25.8, p=0.89). Hospital mortality was not statistically significant between the two groups (32.9% vs. 27.6%, p=0.514). Conclusion: This study suggests similar outcomes for oxygen requirements, hospital length of stay, and mortality between baricitinib and tocilizumab when given in conjunction with remdesivir and steroids for severe COVID-19 pneumonia. Disclosures: Kathy Tin, D.O., Merck: Stocks/Bonds|Novavax: Stocks/Bonds|Pfizer: Stocks/Bonds Roderick Go, DO, Aptose Biosciences: Stocks/Bonds|Bristol Meyers Squibb: Stocks/Bonds|Cytodyn Inc.: Stocks/Bonds|Scynexis: Grant/Research Support.